Loss of genetic diversity in farmed populations of Colossoma macropomum estimated by microsatellites - Santos, C. H.A.; Santana, Givanildo Ximenes; Sá Leitão, C. S.; Paula-Silva, Maria Nazaré N.; Almeida-Val, Vera Maria Fonseca (Animal Genetics, 2016)
The genetic variability of four Colossoma macropomum broodstocks, three from fish farms in different regions and one from the natural environment in Brazil, was analyzed using microsatellite markers. The wild progeny (n = 30) were caught in the Solimões-Amazonas River, at the varzea lakes; this location is used to mature the fish from larvae to juveniles. The three fish farms were selected according to the age of their lineages and broodstock availability: DNOCS (n = 21) is located in the Ceará State, representing the oldest lineage of cultivated tambaqui in Brazil; Balbina (n = 30) is located in the Amazonas State, representing the youngest stocks of tambaqui farmed in Brazil (approximately 15 years); and UFRPE (n = 30) is located in the Pernambuco State and is considered to be a mixed stock formed from the DNOCS and Balbina lineages. The analysis of 13 microsatellite loci indicated the occurrence of a variability reduction in the farmed populations; the UFRPE stock was the population with the highest diversity level. Low values of molecular coancestry were found in these populations. Additionally, significant differences in the RST values among the populations were detected, as was the occurrence of genetic structure. The genetic loss found in these populations may have been influenced by the founder effect. Because no breeding programs were during the entire production period and no pedigree records were kept for these broodstocks, we suggest that a wild population might be used as an important genetic resource to increase the genetic diversity of renewal stock lineages. © 2016 Stichting International Foundation for Animal Genetics.
Keywords: Microsatellite Dna; Allele; Animals; Aquaculture; Brasil; Breeding; Characiformes; Dna Sequence; Founder Effect; Genetic Variation; Genetics; Genetics, Population; Alleles; Animal; Aquaculture; Brasil; Breeding; Characiformes; Founder Effect; Genetic Variation; Genetics, Population; Microsatellite Repeats; Sequence Analysis, Dna